Water absorption measurement of fine porous aggregates using an evaporative method: Experimental results and physical analysis. (February 2018) - Naël-Redolfi, Jennifer; Keita, Emmanuel; Roussel, Nicolas
Abstract: Assessment of the so-called "saturated-surface-dried" state shows a strong dependency on the test operator in the case of fine porous aggregates. This leads to low reliability and reproducibility of water absorption measurement for this family of particles. Evaporative methods for water absorption measurements seem to be a promising alternative. In this paper, we aim at evaluating the robustness and the limit of such methods while understanding the general underlying physical processes. We therefore measure the drying kinetics of non-porous and porous, real and model particles with various sizes and morphologies. We study specifically the unexpected effects of angularity and roughness of particles on drying rate changes over time. Our results suggest that this method is not suitable for all porous particles but shall apply well to crushed fine porous particles such as crushed sand and recycled sand.